Business Model Design of Ranau Tilapia Micro-Enterprise Using the Business Model Canvas Approach - M. Julian Lila; M. Oktavianur (Cita konsultindo, 2026)
This study aims to design an appropriate business model for the Ranau tilapia micro-enterprise Nila Ranau Bang Meng in Bandar Lampung using the Business Model Canvas (BMC) approach. The business operates conventionally and depends on seasonal demand, resulting in sales fluctuations. This research used a qualitative case study method with data collected through observation, in-depth interviews, and documentation. The analysis was conducted by mapping the existing business model into the nine BMC elements and formulating a proposed model. The results show that strategic improvements are needed, particularly in value propositions, channels, customer relationships, and key partnerships. Product innovation, digital and offline marketing, customer relationship strengthening, and partnership expansion are recommended. The study concludes that the Business Model Canvas is an effective tool for developing a more structured and competitive business model for local micro-enterprises.